Perancangan Aplikasi E-Learning Berbasis WEB pada SMA Negeri 5 Batanghari - Ibnu Sani Wijaya; Ali Sadikin; Pareza Alam Jusia; Asri Suryo Widi (LPPM STIKOM Dinamika Bangsa, 2022)
e-learning is one of the learning media which supports the teaching and learning process by using the internet. Currently at SMA Negeri 5 Batanghari the teaching and learning process is carried out during the pandemic using social media such as whatsapp. There are limitations of the whatsapp application so that teaching and learning activities at the school do not go well, such as sending assignments that can carry out automatic assessments. Based on that, it is necessary to develop a web-based e-learning application with the aim of research to make it easier for teachers to send and process grades automatically. The method used in this research is on system development using the waterfall. While the method of data collection is done by interviewing, observing and reviewing the literature into related research. In this research, a web-based e-learning application was produced using the PHP programming language and the MySQL database. The views obtained in this e-learning application are teacher data, student data, grade data, assignment delivery, and reports for teachers in the progress of activities during teaching and learning at SMA Negeri 5 Batanghari. Keywords: Design, Website, E-learning